Donor-acceptor polymers for applications in organic electronics and photovoltaics - Ponce-Ortiz, Rocío; Mayorga-Burrezo, Paula; Casado-Cordón, Juan; López-Navarrete, Juan Teodomiro; Guo, Xugang; Zhou, Nanjia; Facchetti, Antonio; Marks, Tobin J. (My University, 2013)
We have synthesized a new series of high-mobility polymeric semiconductors with good processability and excellent environmental stability for organic electronics and photovoltaics. Using these materials, solar cells were fabricated with power conversion efficiencies of up to 8.7% and remarkable fill factors of 76-80%.
Keywords: Química física; Donor-Acceptor Polymers; Organic Electronics; Photovoltaics; Raman spectroscopy